Educational evaluation and accountability: analysis of articles published in Brazil and Colombia (Práxis Educativa, 2023)
This article aims to explore theoretical references of scientific productions on educational evaluation policies and accountability, through a meta-research exercise. Specifically, the text analyzes articles published in scientific journals in Brazil and Colombia, indexed in databases such as Redalyc or equivalent. The results achieved allowed to verify the low incidence of productions in which the authors explain the epistemological perspective, the epistemological positioning and the reference authors, central aspects in studies of the meta-research type. While this finding exposes some weaknesses in publications on the subject, it highlights a vast field for future studies on theoretical references in scientific production on educational evaluation policies and accountability.Keywords: Educational evaluation. Accountability. Meta-research.